PEDAGOGIKALÍQ DIAGNOSTIKA MASHQALALARÍNÍŃ AYÍRÍM ASPEKTLERI - Allaniyazov, I.B. (SCIENCE and SOCIETY, 2025)
The article considers some results of pedagogical diagnostics and evaluation of students' learning outcomes. The main means and procedures of diagnosis are considered. The advantages and disadvantages of test control of knowledge in comparison with traditional methods of pedagogical diagnostics are revealed.